How does audit committee moderate the relationship between audit firm size, industry specialization, and the cost of equity capital? A comparison of the Ohlson and Capital Asset Pricing Model - Christina Hutabarat, Emayanti; Arifin, Taufiq; Abrar, Afsheen (University of Islam Malang, 2022)
The purpose of this study is to examine the moderation effect of the audit committee on the linkages between audit firm size, industry specialization, and the cost of equity capital with firm size and financial leverage as a control variable. This study is one of few that compared the accuracy of Ohlson and Capital Asset Pricing Model in explaining the cost of equity capital and the moderation role of the audit committee. A sample of 123 manufacturing firm-year observations was drawn from Indonesian-listed companies for five years period (2016-2020). The results show that while the audit committees significantly moderate the negative relationship between firm size on the cost of equity capital, there is no significant evidence of the moderation role of the audit committee on the relationship between industry specialization and the cost of equity capital using the Capital Asset Pricing Model. On the contrary, the moderation role of the audit committees on the effect of industry specialization toward the cost of equity capital under Ohlson was supported in the study. Further, it found that the Ohlson has a better performance than the Capital Asset Pricing Model in explaining the cost of equity capital as the Ohlson measurement expressed the role of earnings per share which represent a more real rate of return.